Adoptive transfer of ex vivo expanded regulatory T cells in an autoimmune hepatitis murine model restores peripheral tolerance1. Issue 1 (1st October 2012) - Lapierre, Pascal; Béland, Kathie; Yang, Roland; Alvarez, Fernando
Abstract Autoimmune hepatitis (AIH) is characterized by a loss of immunological tolerance to hepatocytes. Patients respond well to immunosuppression but progression to endstage liver disease occurs in 10%‐20% of cases, leading to liver transplantation. Using a murine model of type 2 AIH, we identified susceptibility factors for autoimmune hepatitis and attempted to restore immunological tolerance to liver autoantigens. An increased ectopic expression of a liver autoantigen (FTCD) in the thymus leading to reduced numbers of circulating autoreactive T cells was sufficient to prevent development of AIH in mice. However, in the presence of a reduced central tolerance to FTCD, a strong regulatory T‐cell response was able to inhibit proliferation of liver‐specific autoreactive T cells and prevent AIH. Development of a severe AIH stemmed from reduced numbers of functional regulatory T cell (Tregs) leading to an increased proliferation of FTCD‐specific autoreactive T and B cells. Adoptive transfer of ex vivo expanded CXCR3+ Tregs in mice with AIH efficiently targeted the inflamed liver, restored peripheral tolerance to FTCD, and induced remission of AIH. Conclusion: Peripheral tolerance to liver autoantigens in AIH is paramount. Autologous infusion of ex vivo expanded CXCR3+ Tregs in AIH patients could be an effective therapeutic approach to restore peripheral tolerance and induce remission of AIH. (HEPATOLOGY 2013)